The partitions of memory : the afterlife of the division of India - Kaul, Suvir (Delhi : Permanent Black ; Bangalore : Distributed by Orient Longman, 2001)
Contributed articles.
Includes bibliographical references.
Keywords: India -- History -- Partition, 1947.; India -- History -- 1947-